Large AdS6 black holes from CFT5 - Sunjin Choi; Seok Kim (Journal of High Energy Physics)
Abstract We study supersymmetric AdS6 black holes at large angular momenta, from the index of 5d SCFTs on S 4 × ℝ in the large N and Cardy limit. Our examples are the strong coupling limits of 5d gauge theories on the D4-D8-O8 system. The large N free energy scales like N 5/2, statistically accounting for the entropy of large black holes in AdS6. Instanton solitons play subtle roles to realize these deconfined degrees of freedom.